Association between apurinic/apyrimidinic endonuclease 1 rs1760944 T>G polymorphism and susceptibility of cancer: a meta-analysis involving 21764 subjects. Issue 12 (17th December 2019) - Ding, Guowen; Chen, Yu; Pan, Huiwen; Qiu, Hao; Tang, Weifeng; Chen, Shuchen
Abstract: Background: Previous case–control studies have suggested that apurinic/apyrimidinic endonuclease 1 ( APE1 ) rs1760944 T>G polymorphism may be associated with cancer risk. Here, we carried out an updated meta-analysis to focus on the correlation between APE1 rs1760944 T>G locus and the risk of cancer. Methods: We used the crude odds ratios (ORs) with their 95% confidence intervals (CIs) to evaluate the possible relationship between the APE1 rs1760944 T>G polymorphism and cancer risk. Heterogeneity, publication bias and sensitivity analysis were also harnessed to check the potential bias of the present study. Results: Twenty-three independent studies involving 10166 cancer cases and 11598 controls were eligible for this pooled analysis. We found that APE1 rs1760944 T>G polymorphism decreased the risk of cancer in four genetic models (G vs. T: OR, 0.87; 95% CI, 0.83–0.92; P <0.001; GG vs. TT: OR, 0.77; 95% CI, 0.69–0.86; P <0.001; GG/TG vs. TT: OR, 0.83; 95% CI, 0.77–0.89, P <0.001 and GG vs. TT/TG: OR, 0.85; 95% CI, 0.80–0.92, P <0.001). Results of subgroup analyses also demonstrated that this single-nucleotide polymorphism (SNP) modified the risk among lung cancer, breast cancer, osteosarcoma, and Asians. Evidence of publication bias was found in the present study. When we treated the publication bias with 'trim-and-fill' method, the adjusted ORs and CIs were not significantly changed. Conclusion: In conclusion, current evidence highlights that the APE1 rs1760944 T>G polymorphism is a protective factor for cancer susceptibility. In the future, case–control studies with detailed risk factors are needed to confirm or refute our findings.